Da aldeia à cidade: narrativas de identidade de jovens adultos criados na Aldeia SOS de Rio Bonito - Cruz, Helena Maffei (2007)
This research has as theme of study the constitution of the self of young adults raised in shelters under the care of a social-mother in the Aldeia de Rio Bonito, in São Paulo, institution that s linked to the Aldeias Infantís SOS do Brasil. The general objective is to investigate the meanings attributed to the relations in the institution, as constitutive of the identity of young adults who lived there, up to their adulthood, by exploring the meanings attributed to the shelter, social mother, brothers and village the four pillars of the mission of the institution in the self-descriptions of these young people; intends, also to comprehend the relevance of these meanings in their situation of young adults, due to the need to guarantee the self survival, considered as an indicator of adulthood. It is a qualitative research where the researcher studies, based on the narrative of four young people about themselves, the presence of the four pillars of the institution in these self-descriptions. The relational comprehension of the self constitutionf, common to many systemic theories and the social constructionism, which proposes the meaning as socially constructed in language, gives the bases to the analyses and interpretation of the proposed categories and the other categories constructed through the narratives of the interviewees. The results lead to the presence of the people who integrate the net constituted in the Village and from the village as fundamental voices in the co-construction of an experience of the self, in coherence with the time and the space that constitute the identity. Other social voices, such as prejudice, which came up in the interviews, are part of the restricted identity of these young people, as much as the wide social economic context in the city of São Paulo. The research offers reflection about the co-responsibility between the institution and the external social agents on the way from the Village to the city, towards the adulthood of these emancipated young people from the Village